1994
DOI: 10.1128/jvi.68.8.5117-5125.1994
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional structure of baculovirus-expressed Norwalk virus capsids

Abstract: The three-dimensional structure of the baculovirus-expressed Norwalk virus capsid has been determined to a resolution of 2.2 nm using electron cryomicroscopy and computer image processing techniques. The empty capsid, 38.0 nm in diameter, exhibits T=3 icosahedral symmetry and is composed of 90 dimers of the capsid protein. The striking features of the capsid structure are arch-like capsomeres, at the local and strict 2-fold axes, formed by dimers of the capsid protein and large hollows at the icosahedral 5and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
91
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(98 citation statements)
references
References 47 publications
3
91
0
Order By: Relevance
“…There are limitations in NoV VLP production in terms of inadequate yield and quality of the VLPs [1,3,9,20]. Both sucrose and CsCl gradients ultracentrifugation have been used for purification of NoV VLPs [1,7,9,17], even though studies on rotavirus-like particles demonstrated a low yield and impurities resulting from CsCl gradient purification [16].…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…There are limitations in NoV VLP production in terms of inadequate yield and quality of the VLPs [1,3,9,20]. Both sucrose and CsCl gradients ultracentrifugation have been used for purification of NoV VLPs [1,7,9,17], even though studies on rotavirus-like particles demonstrated a low yield and impurities resulting from CsCl gradient purification [16].…”
mentioning
confidence: 99%
“…In the present study, we compared commonly used methods for NoV GII-4 VLP purification [1,14,17] and concentration [6,19], considering the purity, yield, morphological integrity, antigenicity and functionality of the purified VLPs.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The name calicivirus is derived from the Latin calyx, meaning "cup" or "goblet," and refers to the 6)]. These depressions are frequently not clearly visible (e.g., for NV), although structural studies have demonstrated their presence (7). Because of these structural differences and the previous use of IEM to detect these viruses, many of the HuCVs were initially referred to as small, roundstructured viruses (SRSVs).…”
Section: Virus Structure and Genomic Organizationmentioning
confidence: 99%